2023
DOI: 10.1007/s11427-022-2225-3
|View full text |Cite
|
Sign up to set email alerts
|

Herbal small RNAs in patients with COVID-19 linked to reduced DEG expression

Abstract: In China, more than 80% of patients with coronavirus disease 2019 (COVID-19) received traditional Chinese medicine (TCM) as a treatment and their clinical efficacy have been reported. However, the underlying molecular mechanism remains unclear. Previous studies have identified herbal small RNAs (sRNAs) as novel functional components. In this study, a cohort of 22 patients with COVID-19 treated with Toujie Quwen (TQ) granules was analyzed. We observed thousands of herbal small RNAs that entered the blood cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…8,9,14 Previous studies have demonstrated favorable biocompatibility and effectiveness, establishing them as innovative methods for delivering nucleic acids orally. [14][15][16]32,33,35 However, the field is FENG ET AL.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8,9,14 Previous studies have demonstrated favorable biocompatibility and effectiveness, establishing them as innovative methods for delivering nucleic acids orally. [14][15][16]32,33,35 However, the field is FENG ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…30 In response, Jiang's group reported the similarity/shared characteristics between plant and animal non-coding sRNA, revealing some shared RNA sequences, suggesting possible cross-kingdom sharing between plant and animal genomes. [31][32][33] It's worth mentioning that traditional Chinese medicine is effective in treating patients with COVID-19 in China, but the specific mechanism is complex and challenging to clarify. 34 Interestingly, Jiang's group first reported that in the peripheral blood mononuclear cells (PBMCs) samples of COVID-19 patients treated with traditional Chinese medicine, many sRNAs derived from herbal sources were identified.…”
Section: Controversy Regarding Nucleic Acid Molecules Originating Fro...mentioning
confidence: 99%
See 3 more Smart Citations